HUBUNGAN ANTARA KREATIVITAS, KEMAMPUAN NUMERIK DAN SIKAP SISWA TERHADAP PELAJARAN MATEMATIKA DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI SE-KECAMATAN PUNDONG - Esa Gunarti (UNION: Jurnal Ilmiah Pendidikan Matematika, 2017)
Descriptively, the purpose of this research is to know the tendency of creativity, numerical ability, the students’attitude in mathematics and achievement of the students. Correlatively, the purpose is to determine the relationship between creativity, numerical ability, the students’attitude in mathematics with the achievement matematics of the students. The population of this study was all students of VIII of Junior High School in Pundong district on 2013/2014 academic year. The sampling technique used was cluster random sampling. The results of this descriptive study showed that the tendency category of creativity in medium, numerical ability in high, the students’attitude in mathematics in medium and achievement of the students in high. Correlatively, it show R=0,899 its means that there is positive and significant relationship between creativity, numerical ability and the students’attitude in mathematics  with the achievement matematics of the students.